Desain Kerangka Pembelajaran Islam Berbasis Moderasi Beragama Untuk Generasi Muda Muslim Indonesia - Nefi Aprianti (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to examine the design of the Islamic Education learning framework in implementing religious moderation in students through teaching and learning activities in class. The aim is to monitor Islamic religious education learning activities starting from the pre-session stage to the evaluation stage in Islamic religious education learning, seen from the learning planning process, learning implementation, assessment in learning to the evaluation process and follow-up in the learning process in implementing religious moderation as a guide. In this study, a research technique oriented to Social Cognitive Theory (SCT) was used by Albert Bandura which holds that a person learns from direct experience but from events that he witnesses and then he understands to be implemented or imitated. through selective observation and remembering what is conveyed by others in the form of behavior or words that affect their abilities and understanding in the future. In Social Cognitive Theory (SCT) research accuracy and methodological phases are very important. By using the Social Cognitive Theory (SCT) approach, researchers want to be more flexible in knowledge, observation, and research on Planning, Implementation, and Evaluation of Islamic Religious Education Learning Based on Religious Moderation in Islamic Religious Education Teachers and Madrasas or Schools. 73 Islamic Islamic Education teachers and madrasas as well as schools from various schools in Indonesia participated in this study. Examining the three stages of learning, namely planning, implementation, and evaluation, it is known that the Islamic moderation-based learning model applied by teachers in several schools and madrasas in Indonesia is quite good and effective in increasing students’ understanding of the values of religious moderation.